Якість електроенергії в електричних мережах з розподіленим генеруванням - Варецький, Ю.; Пазина, Я.; Наконечний, Я. (Видавництво Національного університету “Львівська політехніка”, 2004)
Decentralized electric power generation is playing a more and more important role in power systems. Decentralized electric power generation or so called distributed generation (DG) can have a significant impact on the power flow and voltage profile in electrical network as well as on power quality indices. This requires a suitable means to analyze the influence of such technologies on the electrical networks. In this paper performance peculiarities of the electrical network including DG are considered.
Keywords: 621.316.761.2